(3SYQ GdUQa h EOGQJg aj Xd GdUOeGJ GdGbJUGOjI (B:s (3fXQjI h JWHjbGJ (B/s - (3GdZGdHj, YHO GdMSjf Ldjd YHO GdMSfs ((3YeGf(B: s (3OGQ UaGA(B, s, 2011)
(3eaghe SYQ GdUQa h GdYhGed GdeDKQI ajg h fXeg , bhGYO GNJjGQ fXGe GdUQa h EOGQJg aj Xd GdUOeGJ GdMbjbjI h GdfbOjI , HGdJWQb Gdi fehPL QhHQJ eGfOjd h adhO h dBNQjf , GdYhGed GdeDKQI aj SYQ GdUQa GdCLfHj JLGg YedGJ HYV GdOhd GdeNJGQI , h EOGQI SYQ GdUQa aj Xd GdUOeGJ GdGbJUGOjI dgPg GdOhd GdeNJGQIs
(3bGFeI GdLOGhd U(B.11(3; bGFeI GdedGMb U(B.14s
Keywords: (3GdGbJUGOs; (3GdfbhOs; (3SYQ GdUQas